Strength and conditioning for cyclists. Off the bike conditioning for performance and life - Burt, P.; Evans, M. (Bloomsbury Sport, 2018)
Phil Burt and Martin Evans have worked with the world's best cyclists, including the Great Britain Cycling Team, devising and implementing highly effective off the bike training plans. Now, in Strength and Conditioning for Cyclists you can benefit from their wealth of knowledge and experience and apply it to make you a stronger, faster and more robust cyclist.